Antimicrobial Silver in Medicinal and Consumer Applications: A Patent Review of the Past Decade (2007-2017) - Wilson Sim; Ross T. Barnard; M.A.T. Blaskovich; Zyta M. Ziora (MDPI AG, 2018)
The use of silver to control infections was common in ancient civilizations. In recent years, this material has resurfaced as a therapeutic option due to the increasing prevalence of bacterial resistance to antimicrobials. This renewed interest has prompted researchers to investigate how the antimicrobial properties of silver might be enhanced, thus broadening the possibilities for antimicrobial applications. This review presents a compilation of patented products utilizing any forms of silver for its bactericidal actions in the decade 2007-2017. It analyses the trends in patent applications related to different forms of silver and their use for antimicrobial purposes. Based on the retrospective view of registered patents, statements of prognosis are also presented with a view to heightening awareness of potential industrial and health care applications.